FRAGRANCE COMMUNICATION THEORY: How Scent Speaks - Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
One of the sensors that plays a vital role in communication is the sense of smell, which transmits nasal messages. A form of nasal communication that is widely used in everyday and professional activities is fragrance communication. This article focuses on dissecting the six dimensions of fragrance communication: Message (a special message sent by the communicator to the communicant regarding the fragrance), Memory (fragrances that lead someone to specific memories), Mood (fragrances that can create or change the mood of the wearer or people surroundings that capture the fragrance), Me (fragrance as the identity and personality of someone or something unique), Mate (fragrance as an attractant and binding social relationship between actors and communication reactors), and Myth (fragrance as a signifier of myths that develop in a particular culture and society). Fragrance communication is the process of constructing and interpreting meaning through the sense of smell involving sensation stimuli and nasal perception. To cite this article (7th APA style): Wijaya, B. S.. (2018). Fragrance Communication Theory: How Scent Speaks. Journal Communication Spectrum: Capturing New Perspectives in Communication, 8(1), 94-113. http://dx.doi.org/10.36782/jcs.v9i2.1958